POLITIK HUKUM TERHADAP TINDAK PIDANA PENISTAAN AGAMA OLEH TOKOH PUBLIK - Putra, Haekal Amalin Firdany (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The objective of this study is to examine how political law impacts the enforcement of law in cases of religious defamation by public figures, with a particular focus on the Basuki Tjahaja Purnama (Ahok) case. The research question is: does political law affect the enforcement of law in blasphemy cases involving public figures, as seen in Decision Number 1537/Pid.B/2016/PN.Jkt.Utr, This research employs a normative juridical approach, utilizing both legislative analysis and case studies. Data is gathered through literature reviews, and court decisions are analyzed qualitatively. Conclusions are drawn using deductive reasoning. The findings indicate that political law plays a significant role in influencing the law enforcement process and outcomes in the Ahok case. Despite the existence of substantive laws in Law No. 1/PNPS/1965 and Article 156a of the Criminal Code, the study reveals that public pressure and political dynamics have impacted the legal proceedings. This reflects a discrepancy between the ideal legal framework (das sollen) and its actual implementation (das sein) in Indonesian legal practice.Keywords: Legal Politics, Blasphemy, Public Figures.